RELATIONSHIP BETWEEN ETHICAL LEADERSHIP, JOB SATISFACTION ANDJOB PERFORMANCE - Shehzad, Dr. Naveed; Khan, Dr. Muhammad Imran; Khan, Shafqat (The journal of contemporary issues in business and government, 2022)
Nowadays universities are going through the transition due which new performance standards have been created. In such situation, performance of employees can be enhanced through effective ethical leadership. The current study has examined the dynamic links between job satisfaction, job performance and ethical leadership in the academia of Pakistan. Using a cross sectional design, quantitative data were collected from 150 academic staff working in three universities. Data were analyzed both by descriptive and inferential statistics. The results showed that four characteristics, i.e., practicing preacher; safe haven creator; moral motivator and ethical justice were positively associated with job performance, whereas this link was partially mediated by job satisfaction. The results obtained were in a strong concurrence with the existing literature. Hence, universities of Pakistan should focus on developing ethical leadership among their employees. In this way, universities can grow and contribute towards the socioeconomic development of Pakistan.